Hazards to livestock of consuming aflatoxin-contaminated groundnut meal in Africa - Reed, J.D.; Kasali, O.B. (International Crops Research Institute for the Semi-Arid Tropics, 1989)
Summarises the history and occurance of aflatoxins in groundnut meal. Looks into the clinico-pathologic features of aflatoxins and discusses its effects on ducks, poultry, swine and ruminants as well as the implications of using groundnut meal as a feed in Africa.